• Matéria: Matemática
  • Autor: nicollette220
  • Perguntado 9 anos atrás

como resolve essa conta?
(6⁻¹)⁴

Respostas

respondido por: Anônimo
3
(6^{-1})^4=(\frac{1}{6})^4=\frac{1^4}{6^4}=\boxed{\frac{1}{1296}}
respondido por: Anônimo
0
[   - 1   ]  4                (-1).4              - 4
[6        ]         =     6                 =   6

         - 4
=   6           =      1                  1
                      --------   =  --------------
                             4            1296
                          6

Perguntas similares